Akuntansi UMKM Kuliner di Kota Makassar: Sebuah Metafora "Dari Dapur Tradisional ke Restoran Digital" - Nur Fadhila Amri; Faridah Faridah; Thanwain Thanwain; A. Nur Azizah Fajry Azzahrah; Moh Arya Adiwangsa (Jurnal Riset Akuntansi, 2026)
The shift from manual and informal bookkeeping practices to technology-supported structured financial management in small and medium enterprises within the framework of the evolution of culinary MSME accounting practices by considering the typical socio-cultural context. The study aims to explore the transformation of accounting practices in culinary Micro, Small, and Medium Enterprises (MSMEs) in Makassar, Indonesia, through the metaphor "From Traditional Kitchens to Digital Restaurants." Using a mixed methods approach, this study integrates Pierre Bourdieu's theory of social practice to analyze the shift from informal manual bookkeeping to digital accounting systems sociologically, taking into account how habitus, capital, and social structure influence accounting adoption. The survey of 3,950 culinary MSMEs was complemented by qualitative interviews with 95 business owners. The findings highlight significant gaps in accounting practices, which are influenced by digital access, cultural capital, and social habits. Digital adoption improves financial reporting and profitability but remains uneven due to social and educational constraints. The study recommends targeted digital literacy programs and policy incentives to bridge the gap.